Covid 19 pandemic and Abnormal Stock Returns of listed companies in Vietnam - Dang Ngoc Hung; Vu Thi Thuy Van; Chi Le Van (Cogent Business & Management, 2021)
Covid-19 pandemic is affecting the health of the public, and it is also impacting business and economy. The main objective of this paper is to investigate the impact of Covid-19 pandemic on listed firms' performance and the abnormal stock returns in Vietnam. To study the impact of Covid-19 on firms' performance, we collected data about announced earnings on Q1/2020 and Q4/2019 of 714 enterprises and made comparison. The results revealed the enormous impacts of Covid-19 pandemic on the business performance. However, the level of influence varies among sectors. To study the impact of Covid-19 on the abnormal stock returns, the study employed the event research method with 3 events related to Covid-19 pandemic in Vietnam. A sample of 364 companies listed on Ho Chi Minh Stock Exchange (HOSE) was utilized. The findings revealed that the Covid-19 event affects the abnormal returns of stocks and the level of influence varied from each stage of Covid-19 prevention measure in Vietnam. The degrees of influence of the Covid-19 event on each stock were also different. The paper concluded that Covid-19 pandemic information can be used to predict stocks' prices.
Keywords: G12; G14; 650; Covid-19 pandemic; firms’ performance; stock return; earnings; event study